Berberine alleviates liver fibrosis through inducing ferrous redox to activate ROS-mediated hepatic stellate cells ferroptosis - Jiazhi Yi (Nature Publishing Group, 2021)
Abstract Berberine (BBR) has been explored as a potential anti-liver fibrosis agent, but the underlying mechanisms are unknown. In the current study, we aimed to investigate the molecular mechanisms underlying the effect of BBR against liver fibrogenesis in thioacetamide (TAA) and carbon tetrachloride (CCl4) induced mouse liver fibrosis. In addition to i.p. injection with TAA or CCl4, mice in the treatment group received BBR intragastrically. Concurrently, combined with TAA and BBR treatment, mice in the inhibitor group were injected i.p. with ferrostatin-1 (Fer-1). Hepatic stellate cells (HSCs) were also used in the study. Our results showed that BBR obviously alleviated mouse liver fibrosis and restored mouse liver function; however, the pharmacological effects of BBR against liver fibrosis were significantly diminished by Fer-1 treatment. Mechanically, BBR impaired the autophagy–lysosome pathway (ALP) and increased cell reactive oxygen species (ROS) production in HSCs. ROS accelerated the breakdown of the iron-storage protein ferritin and sped up iron release from ferritin, which resulted in redox-active iron accumulation in HSCs. Lipid peroxidation and glutathione (GSH) depletion triggered by the Fenton reaction promoted ferroptosis and attenuated liver fibrosis. Furthermore, impaired autophagy enhanced BBR-mediated ferritin proteolysis to increase cellular ferrous overload via the ubiquitin–proteasome pathway (UPS) in HSCs and triggered HSC ferroptosis. Collectively, BBR alleviated liver fibrosis by inducing ferrous redox to activate ROS-mediated HSC ferroptosis. Our findings may be exploited clinically to provide a potential novel therapeutic strategy for liver fibrosis.